The Drivers of carbon emissions in emerging economies: Empirical analysis of selected ASEAN countries using panel data approach - Wong, Zhan Han (The Asian Journal of Technology Management (AJTM), 2024)
Abstract.  This study investigates the influence of Artificial Intelligence (AI) implementation on recruitment outcomes, focusing on the mediating role of candidate experience and the moderating effects of trust in AI and organizational culture. Using a quantitative research design, data were collected from HR professionals across various industries in Indonesia. The results reveal that AI implementation positively affects candidate experience and quality of hires, with candidate experience acting as a significant mediator in these relationships. Trust in AI is found to play a dual role, both directly influencing candidate experience and quality of hires and moderating the relationship between AI implementation and candidate experience. Organizational culture, particularly an innovation-oriented culture, strengthens the impact of AI implementation on candidate experience. The study contributes to the theoretical understanding of candidate experience as a higher-order construct and highlights the importance of trust and cultural alignment in AI-driven recruitment. Practical implications emphasize the need for transparent AI systems, regular feedback, and fostering an innovation-oriented culture to enhance recruitment outcomes. Limitations include the cross-sectional design and the focus on a single country, suggesting opportunities for future research to explore longitudinal effects and cross-cultural comparisons.  Keywords: Artificial intelligence, candidate experience, trust, organizational culture, quality of hires